Compaction of fly ash–aluminum alloy composites and evaluation of their mechanical and acoustic properties - Hrairi, Meftah; Ahmed, Mirghani Ishak; Nimir, Yassin (Elsevier, 2009)
The density and elastic moduli of green compacts can be determined by ultrasonic method with the help of pre-prepared diagrams. In this way, pressing conditions can be taken under control easily. In this study, fly ash particles were used as fillers in an aluminum alloy matrix material. The weight fractions of fly ash in the composites were in the range of 5–30%. The resulting composites were compacted at pressures ranging from 63 MPa to 316 MPa. It was observed that the green density increased with increasing compacting pressure and decreased with increasing weight percent of fly ash particles resulting in lightweight composites. The green compact composites were also tested using an ultrasonic nondestructive evaluation method. Results showed that ultrasonic velocities are a strong function of the density and the fly ash fraction in this material and could be potentially used to predict the density and the fly ash fraction as well as the elastic moduli of the metal matrix composite.